PERHITUNGAN, PENYETORAN DAN PELAPORAN PAJAK HOTEL DAN RESTORAN SERTA KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH - FELGI FITRIA MARCELLIN; NOVIA WIJAYA (Jurnal Bisnis dan Akuntansi, 2019)
The purpose of this research is to know the mechanism and the appropriatness of calculation, payment, and reporting of Tax Hotel and Restaurant to the regulation of Bekasi City Number 14 and 8 in 2011, the effectiveness of Hotel Tax revenue and Restaurant Tax revenue in Bekasi City in 2014-2016, and contribution of Tax Hotel and Restaurant to local revenue of Bekasi City in 2014-2016. This research is to check the appropriation between the real implementation of Hotel Tax and Restaurant Tax and the implementation of Hotel Tax and Restaurant Tax has regulated, in accordance to the tax regulation of Bekasi City Number 14 and 8 in 2011. The method used in this research is descriptive analysis. Data ini this research was obtained from Badan PendapatanDaerah in Bekasi City. The data consist of SPTPD, SSPD, Planning and Realization of Hotel Tax and Restaurant Tax, Planning and Realization of local revenue. The result of this search show the mechanism of calculation, payment, and reporting of Tax Hotel and Restaurant of Bekasi City in 2014-2016 are appropriated to the Regulation of Bekasi City Number 14 and 8 in 2011 and other regulations. The effectiveness grade of Hotel tax and Restaurant tax revenue in Bekasi City 2014-2016 are very effective. Meanwhile, the contribution grade of Hotel tax and Restauran tax to local revenue in 2014-2016 is has less criteria for restaurant tax and very less criteria for hotel tax.